(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
This article is a continuation of the chronicled outline of corporate social obligation (CSR), occurred in the twentieth century. The primary definitions, standards, activities were clarified with the reason for research the impact if the sorts of obligations as lawful, moral, charitable on the practical improvement of the endeavor. The resulting CSR ideas perceptions are introduced, to be specific Social Responsibility of Business Man, Stakeholder Approach, Three dimensional model, Three-dimensional model of standards, strategies and cycles, Institutional system and expanded corporate activities, Three-spaces approach, Contemporary idea. The new XXI hundreds of years SCR ideas were found and their speculations fixed. Novel experiences into contemporary importance of SCR are being recommended.